Dance studies in China : selected writings from the Journal of Beijing Dance Academy - Deng, Youling; Zhang, Yanjie; Cai, Shuo; Zhao, Yuting (Intellect China Library series., 2022)
A collection of articles selected from the Journal of Beijing Dance Academy, translated here for an English-speaking audience. Beijing Dance Academy is a full-time institution of higher learning with commitment to developing excellent professional dancers, choreographers and dance researchers. Part of the Intellect China Library series.